Pain and Menopause Symptoms of Breast Cancer Patients with Adjuvant Hormonal Therapy in Korea: Secondary Analysis - Myungsun Yi; Eunkyung Hwang (Asia-Pacific Journal of Oncology Nursing, 2018)
Objective: The purpose of this study was to describe the prevalence and levels of pain and menopause symptoms of breast cancer patients with adjuvant hormonal therapy (HT). Methods: A cross-sectional survey design was used. Secondary analysis was used from the primary data collected in 2013 from a total of 110 breast cancer patients receiving HT for more than 3 months, using questionnaires of the Korean version of brief pain inventory and the menopause rating scale. Results: Mean age of the participants was 53.56. Most (88.2%) of the participants reported to have pain and almost (95.5%) of them reported to have menopause symptoms. More pain was reported in participants with aromatase inhibitor (AI) than those with tamoxifen. Adherence to HT showed a significant difference according to the rate of feeling increased pain (P = 0.001). Among the menopause symptoms, fatigue was the most common symptom (97.3%). Sweating/flush was significantly higher in tamoxifen group (P < 0.005), and joint and muscle complaints were higher in AI group (P < 005). Conclusions: The results of the study show that the prevalence and levels of pain and menopause symptoms among breast cancer patients receiving HT were high. Thus, oncology professionals need to provide appropriate interventions to relieve pain and menopause symptom to improve adherence to HT.